Beta‐ray imaging system with γ‐ray coincidence for multiple‐tracer imaging. Issue 2 (25th December 2019) - Fukuchi, Tomonori; Yamamoto, Seiichi; Kataoka, Jun; Kamada, Kei; Yoshikawa, Akira; Watanabe, Yasuyoshi; Enomoto, Shuichi
Abstract : Purpose: Beta‐ray imaging systems are widely used for various biological objects to obtain a two‐dimensional (2D) distribution of β‐ray emitting radioisotopes. However, a conventional β‐ray imaging system is unsuitable for multiple‐tracer imaging, because the continuous energy distribution of β‐rays complicates distinguishing among different tracers by energy information. Therefore, we developed a new type of β‐ray imaging system, which is useful for multiple tracers by detecting coincidence γ‐rays with β‐rays, and evaluated its imaging performance. Methods: Our system is composed of position‐sensitive β‐ray and γ‐ray detectors. The former is a 35 × 35 × 1‐mm 3 Ce‐Doped((La, Gd)2 Si2 O7 ) (La‐GPS) scintillation detector, which has a 300‐µm pitch of pixels. The latter is a 43 × 43 × 16‐mm 3 bismuth germanium oxide (BGO) scintillation detector. Both detectors are mounted on a flexible frame and placed in a user‐selectable position. We experimentally evaluated the performance of the β‐ray detector and the γ‐ray efficiencies of the γ‐ray detector with different energies, positions, and distances. We also conducted point sources and phantom measurements with dual isotopes to evaluate the system performance of multiple‐tracer imaging. Results: For the β‐ray detector, the β‐ray detection efficiencies for 45 Ca (245‐keV maximum energy) and 90 Sr/ 90 Y (545 and 2280‐keV maximum energy) were 14.3% and 21.9%, respectively. The total γ‐ray detection efficiency of the γ‐ray detector for all γ‐rays from 22 Na (511‐keV annihilation γ‐rays and a 1275‐keV γ‐ray) in the center position with a detector distance of 20 mm was 17.5%. From a point‐source measurement using 22 Na and 90 Sr/ 90 Y, we successfully extracted the position of a positron‐γ emitter 22 Na. Furthermore, for a phantom experiment using 45 Ca and 18 F or 18 F and 22 Na, we successfully extracted the distribution of the second tracer using the annihilation γ‐ray or de‐excitation γ‐ray coincidence. In all the imaging experiments, the event counts of the extracted images were consistent with the counts estimated by the measured γ‐ray efficiencies. Conclusions: We successfully demonstrated the feasibility of our β‐ray autoradiography system for imaging multiple isotopes. Since our system can identify not only a β‐γ emitter but also a positron emitter using the coincidence detection of annihilation γ‐rays, it is useful for PET tracers and various new applications that are otherwise impractical.